PENGARUH LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA PRESTASI KERJA DI HOTEL INNA GARUDA YOGYAKARTA - Prasetyanto, Hermawan (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2012)
The purpose of this researched was to found both direct or indirect the influence of jobs atmosphere, and leadership style variable toward employee’s performance through job satisfaction at Hotel Inna Garuda Yogyakarta. The data used in this research was primary data which consists of 7 dimensions with 11 indicators for jobs Atsmosphere variable. 5 dimensions with 11 indicators for Leadership Style variable. 5 dimension with 11 indicators for satisfaction variable, and 3 dimension with 11 indicators for job performance variable. The method of collecting data was ganited by questionnaires deployment to 70 respondent by quantitative and qualitative descriptive. The result of the data analysis described that all of hypothesis was acceptable. It is indicate that the Corporate Culture, and Leadership Style variable have positively and significantly infruenced toward the job satisfaction, and based on the result of path analysis ( direct and indirect) that those variable were found directly dominant influenced toward the employye’s performance than through the job satisfaction. Key word : Job’s Atsmosphere, Ladership Style, Job satisfaction, and Employee’s Perfomance.